The grief experiences and needs of bereaved relatives and friends of older people dying through suicide: A descriptive and case-control study - Hanvood, D; Hawton, K; Hope, T (2002)
Background: The grief experiences of those bereaved through the suicide of older persons are largely unknown. Legal procedures surrounding the death are a possible source of distress. In addition, research suggests that feelings of guilt, as well as a sense of stigma, shame, or rejection, are more common in relatives bereaved through suicide than in individuals bereaved through other modes of death. Method: In a cohort of 85 friends and relatives of older individuals (a 60 years) who committed suicide, problems encountered during legal procedures following the death and grief experiences were examined. In addition, the study included a case-control comparison of the bereavement reactions of a subgroup of these individuals (N = 46) and a control group of individuals bereaved through the natural death of an older person. Interviews were carried out 6 to 21 months after the death; these included a semistructured assessment of problems following the death, the Grief Experience Questionnaire (GEQ), and the Montgomery-Asberg Depression Rating Scale. Results: Among those bereaved through suicide, 36 (42.4%) reported problems related to dealings with the coroner's office, and 33 (38,8%) reported stress due to media reporting of the inquest. Although individuals bereaved through suicide had depression scores similar to those of individuals in the control group, the former group had higher scores on the GEQ subscales measuring stigmatization, shame, sense of rejection, and "unique reactions." Limitations: This study had a low participation rate of potential subjects, especially for the control group. There were differences between the study and control groups in proportions of different kinships to the deceased. Con clusions: Relatives bereaved through suicide frequently experience distress related to media reporting of coroner's inquests and to inquest procedures. These relatives often experience stigma, shame, and a sense of rejection; counseling of these individuals, therefore, should address these themes.